Pembinaan Keluarga Sakinah Dalam Perspektif Dakwah - Malik, Saeful; Ulfain, Ulfain (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2020)
The purpose of this study was to determine the implementation of the sakinah family development in the da'wah perspective at the Kantor Urusan Agama (KUA) Lemahabang District, Cirebon Regency. This research uses constructivism paradigm by using qualitative method and case study approach. Data collection techniques used include: observation, in-depth interviews, and documentation studies. The data analysis technique used in this study is a qualitative descriptive analysis technique. Meanwhile, the validity of the data was checked using the source triangulation technique. The resultsof this study indicate that the implementation of sakinah family development in the Kantor Urusan Agama (KUA) Lemahabang District, Cirebon Regency is carried out according to the vision and mission, goals, subjects and objects, and implements the theory of da'wah based on the al-Quran and hadist.